Simultaneous adsorption of phenol and nickel from wastewater using tea fiber waste - Karania, Gunjal; Singh, Paridhi; R. Girish, C (International Journal of Engineering and Technology, 2018)
The present work explores the potential of tea fibre waste as an adsorbent to remove phenol and nickel from wastewater in both single and binary component mode. The properties of the tea fibre such as surface area, pore volume and particle size were improved by treating with hydrochloric acid. The isotherm models were verified for single component system to find the adsorption mechanism. The equilibrium data were obeying Freundlich model. The simultaneous adsorption of two pollutants were carried out in order to evaluate the interaction mechanism such as synergic, antagonistic or non-interaction effect. It was observed that overall the system was exhibiting synergistic type of behavior.Â Â